ANALISIS INFLASI, TINGKAT BUNGA, DAN NILAI TUKAR PADA RETURN PASAR DI BURSA EFEK INDONESIA - Nurmala, Nurmala (Universitas Muhammadiyah Palembang, 2018)
This study aims to determine the effect of inflation, interest rate and exchange rate on market return in Indonesian Stock Exchange. In this study, researchers used secondary data from inflation rate, interest rate and exchange rate from the Composite Stock Price Index (IHSG) from Bank Indonesia and Idx. The population in this study was the joint stock price movements of companies registered in Indonesian Stock Exchange, while samples used are purposive random sampling with the criteria of Indonesian securities listed companies, stock movement volume traded (CSPI), companies owning shares (including in the CSPI) period of 2012 – 2017. The analysis tool used is multiple regression analysis t-test, F-test and coefficient of determination tested by classic assumption test. The results of the study show Inflation, Interest Rate, Exchange Rate of Stock Return is 0.13. This singnification number is greater than 0.05 which means that the Inflation X1 variable, Interest Rate X1, Exchange Rate X3 does not significantly influence Market Return. Thus H4,which says that inflation, interest rate, exchange rate significantly influence market return are rejected. While partially tested that the significance of inflation is 0.167. This signification number is greater than 0.05 (prob> 0.05). Then H0 is accepted and Ha is rejected so that it can be concluded that inflation does not have a significant effect on Market Return.While the calculation and variable analysis of interest rate is obtained by a result of 0.005. Significance figures obtained are smaller than alpha 0.05 (prob <0.05). This means that the variable interest rate has a significant effect on market return. Thus, it can be concluded that Ho is rejected and Ha is accepted. From the calculation of data analysis there are significant numbers. Whereas, for the exchange rate variable is 0.105. The probability value obtained is greater than alpha 0.05 (prob> 0.05). Then the conclusion is that H0 is accepted and Ha is rejected so that it can be concluded that the exchange rate does not have a significant effect on Market Return.